A novel dressing with silver to treat meticillin-resistant Staphylococcus aureus biofilm infection in a pig model. (1st February 2022) - Davis, Stephen C; Li, Jie; Gil, Joel; Valdes, Jose; Solis, Michael; Higa, Alex
Abstract : Objective: The purpose of this study was to use an in vivo biofilm porcine model to examine a new polyvinyl alcohol-based gelling fibre dressing with silver and compare it to other commercial dressings containing: polyvinyl alcohol-based gelling fibre without silver; carboxymethyl cellulose-based fibre with silver, benzethonium chloride and ethylenediaminetetraacetic acid; and untreated control. Methods: A total of 52 deep partial-thickness wounds (10x7x0.5mm) were created on each of three animals and inoculated with 25µl of meticillin-resistant Staphylococcus aureus (MRSA) (10 6 colony forming units (CFU)/ml). Wounds were covered for 24 hours to allow biofilm formation and were randomly designated to one of the four treatments. Samples were recovered for microbiological and histological analysis on days 3, 5 and 7 post-treatment. Results: Polyvinyl alcohol-based gelling fibre dressing with silver was able to significantly reduce biofilm more effectively than the other treatment groups. By day 7, wounds treated with the dressing had a 2.72±0.01 log CFU/g reduction in MRSA count versus untreated control wounds and a 2.59±0.01 log CFU/g reduction versus baseline counts. For histology analysis, all wounds reached 100% re-epithelialisation by day 5. Conclusion: The results of this study indicated that polyvinyl alcohol-based gelling fibre dressing with silver was effective against biofilm of antibiotic-resistant staphylococcal strains without inhibiting the wound healing process, and may have important clinical implications when treating acute and/or hard-to-heal wounds.